Potential solid waste conversion for power generation (with case studies in Pekan and Rompin) - Amran, Kamarudzaman (2013)
This thesis deals with a study of potential solid waste conversion to generate energy. The study was conducted in Pekan and Rompin. The first objective is to study solid waste management in Malaysia. The second objective is to study the changing technology of solid waste to energy and it's potential in generating alternative energy sources. Methodology used in this study is visit Pekan and Rompin landfill to collect data. Data obtain is used as evident that solid waste in Malaysia increase by year. Except that, we also refer to other's country journal to obtain information and to compare solid waste management system used. Base on this study, there are three method solid waste management in Malaysia, namely open dumping, sanitary landfill and incinerators. Among the three methods of waste management in Malaysia, incinerator is the method which could potentially be used to produce electricity where combustion of solid waste can produce heat. The heat produced can be used in moving the steam turbine. Then, steam turbine can turn the generator to generate electricity. The study also proposed Plasma Gasification as the solution for solid waste management because this method can produce electrical energy, does not require landfill and produce useful by-product tiles, bricks and tar. This study also proposed to apply 3R method from early stage and become everyday practice.